Audience Perception on the Impact of Television Reality Shows on the Moral Lives of Adolescents in Taraba State - Lucas, Joseph M.; Lazarus, Siman (International Journal of Humanities, Education, and Social Sciences, 2024)
This study titled “Audience perception on the impact of television reality show on the moral lives of adolescents in Taraba State, Nigeria,” aims to examine audience’s perceived view about the moral impact of the show(s) on adolescents in Taraba State especially on those in their developmental stage. The study was anchored on the Perception theory to provide support for ongoing discussion. The study was contingent on a dual research method, utilizing survey (quantitative) and In-depth interview (qualitative) research designs. The study’s population comprises of respondents resident in Taraba State who are audiences of television reality show(s). A sample size of 384 respondents was determined using the Taro Yamane’s determinism sampling technique. Multi stage sampling method was employed to select three Local Governments in the strata from the three senatorial district of the State, while simple random sampling was used to select the wards as well as the proportional sampling method was utilized to get numbers of respondents who are audience of television reality show in the three stratums. Findings from the study shows that adolescents in Taraba State have access to television reality show and can form a reasonable opinion about the show. Findings also indicate that, the Big Brother Naija, the Nigerian Idol, and the Voice Nigeria among others are the various television reality shows that adolescents in Taraba State have access to. The study concludes that since television reality shows has the potency to influence and sway ideas, programme packaging and design of the show should be tilted towards building learning and promoting excellence instead of obscenity, nudity and materialism. It is therefore recommended, among others, that content creators, stakeholders and government parastaltas in liaison with the ministry of Arts and Entertainment should work together, prioritize television reality shows, develop and broadcast a TV show that reflects the true nature of the Nigerian society and that are value oriented.